Two crystal forms of GL-V8 and preparation method thereof
By screening and preparing the two crystal forms of GL-V8, the problem of lack of GL-V8 crystal forms in the prior art was solved, and a drug crystal form with high stability, appropriate solubility and moisture-induced properties were obtained, ensuring the bioavailability and therapeutic effect stability of the drug.
Patent Information
- Application Number
- CN202411798066.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-14
AI Technical Summary
The lack of crystalline screening of GL-V8 in the prior art leads to uncertainty in drug solubility and bioavailability, affecting the efficacy and storage stability of the drug.
Two crystal forms of GL-V8 and their preparation methods are provided. The structure and stability are determined by X-ray powder diffraction, differential scanning calorimetry analysis and thermogravimetric analysis. The preparation method includes heating, dropping and cooling treatment in different solvents.
The obtained crystal form has good stability, solubility and moisture-induced properties meet the medicinal requirements, avoiding drug transformation, ensuring the stability of bioavailability and efficacy, and reducing the cost of storage and quality control.
Smart Images

Figure CN119613366A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of pharmaceutical chemistry, and specifically relates to two GL-V8 crystal forms and preparation methods thereof. Background Art
[0002] GL-V8 is a derivative of the flavonoid compound wogonin, with a molecular formula of C 24 H 29 NO7, whose chemical name is 7-(4-(bis(2-hydroxyethyl)amino)butoxy)-5-hydroxy-8-methoxy-2-phenyl-4H-chromene-4-one, has a structural formula as shown in formula (I).
[0003]
[0004] Studies have shown that GL-V8 has a wide range of pharmacological activities and has broad application prospects in the preparation of drugs for the prevention and treatment of liver fibrosis, sepsis, colitis, etc. At the same time, studies have found that GL-V8 has a unique mechanism of action in killing tumor cells. In recent years, as researchers at home and abroad have conducted in-depth research on GL-V8 in the treatment of leukemia from different aspects, GL-V8 has great potential to become a new drug for the treatment of leukemia.
[0005] As we all know, different crystal forms of the same drug often lead to differences in drug solubility, which can cause differences in drug dissolution and bioavailability, thereby affecting the absorption and utilization of the drug in the body, and then causing differences in drug efficacy. Therefore, crystal form is one of the primary issues to pay attention to when selecting dosage forms in drug development, and it is also one of the keys to whether the drug can be effectively absorbed. In addition, the characteristics of the drug crystal form can be used to determine the formulation process, improve the performance of solid drug preparations, and effectively ensure the drug equivalence between production batches. Therefore, screening crystal forms is crucial for subsequent drug development.
[0006] However, there are no reports on the GL-V8 crystal form. Therefore, it is necessary to conduct a comprehensive and systematic polymorph screening of GL-V8 to select the most suitable crystal form for drug development. Summary of the invention
[0007] The purpose of the present invention is to solve the deficiencies in the prior art and provide two crystal forms of GL-V8 and a preparation method thereof.
[0008] The crystal form of the invention has good stability, and its solubility and hygroscopicity meet the requirements for pharmaceutical use. In addition, the preparation method is simple and the cost is low, which is of great value to the optimization and development of the drug in the future.
[0009] In order to achieve the above object, the present invention is achieved through the following technical solutions:
[0010] In the first aspect, the present invention provides a GL-V8 crystal form, which is a crystal form I. In the X-ray powder diffraction spectrum detected by Cu-Ka radiation, 2 θ There are diffraction peaks at 4.0914°, 6.8803°, 9.4388°, 12.5661°, 13.8249°, 16.0123°, 19.1575°, 22.5009°, 23.5099°, 24.0082°, 24.5017°, and 25.6877°. θ The value accuracy is ±0.2°.
[0011] According to differential scanning calorimetry analysis, an endothermic peak begins to appear when Form I is heated to 133.23°C.
[0012] According to thermogravimetric analysis, when Form I is heated to 105.04°C, the weight loss is 2.473%.
[0013] Form I is an anhydrate and a non-solvate.
[0014] In addition, a method for preparing the GL-V8 crystal form I is provided, the method comprising the following steps:
[0015] Add GL-V8 to solvent a; heat to 35-100°C, slowly drop solvent b, keep warm and stir; slowly cool to -20-60°C, stir for 0.5-5 hours, precipitate solid, filter and dry to obtain GL-V8 crystal form I, wherein solvent a is selected from one or a mixture of two or more of ethanol, methanol, isopropanol, DMF, DCM, THF or acetone, and solvent b is selected from one or a mixture of two or more of methanol, isopropyl ether or methyl tert-butyl ether;
[0016] Alternatively, add GL-V8 to solvent a, heat to 35-100°C and keep warm; slowly cool to -20-60°C, stir for 0.5-5 hours, precipitate solid, filter and dry to obtain GL-V8 crystal form I;
[0017] The volume ratio of solvent a to solvent b is 1:1-10; the mass volume ratio of GL-V8 to solvent a is 1:1-20, and the unit is g / mL.
[0018] In the second aspect, the present invention provides a GL-V8 crystal form, which is crystal form II. In the X-ray powder diffraction spectrum detected by Cu-Ka radiation, 2 θ There are diffraction peaks at 4.2870°, 6.5855°, 9.5828°, 11.4800°, 13.1891°, 17.9260°, 18.3199°, 21.9220°, 22.6016°, 24.5669°, 24.8689°, 26.6093°, and 27.5103°. θThe value accuracy is ±0.2°.
[0019] According to differential scanning calorimetry analysis, an endothermic peak began to appear when Form II was heated to 124.38°C.
[0020] According to thermogravimetric analysis, when Form II is heated to 105.04°C, the weight loss is 2.518%.
[0021] Form II is an anhydrate and a non-solvate.
[0022] In addition, the present invention provides a method for preparing the GL-V8 crystal form II, the method comprising the following steps:
[0023] Add GL-V8 to solvent c; heat to 35-100°C, slowly add water, keep warm and stir; slowly cool to -20-60°C, stir for 0.5-5 hours, precipitate solid, filter and dry to obtain GL-V8 crystal form II, wherein solvent c is selected from ethanol, methanol, isopropanol, acetone, DMF or THF, a mixture of one or more thereof;
[0024] The volume ratio of solvent c to water is 1:1-5; the mass volume ratio of GL-V8 to solvent c is 1:1-20, and the unit is g / mL.
[0025] The present invention has the following beneficial effects: (1) The crystal form provided by the present invention has good stability, which can effectively avoid crystal transformation during drug storage and development, thereby avoiding changes in bioavailability and efficacy.
[0026] (2) The crystal form I provided by the present invention is slightly hygroscopic, meets the requirements of bioavailability and efficacy, is not easily affected by humidity, has no stringent requirements on storage conditions, is convenient for long-term storage, greatly reduces the cost of material storage and quality control, and has strong economic value. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is the X-ray powder diffraction spectrum of Form I of GL-V8 obtained in Example 1 (a before stability sampling, b after stability sampling).
[0028] Figure 2 This is the X-ray powder diffraction spectrum of Form II of GL-V8 obtained in Example 6 (a before stability sampling, b after stability sampling).
[0029] Figure 3 This is the DSC spectrum of Form I of GL-V8 obtained in Example 1.
[0030] Figure 4 This is the DSC spectrum of Form II of GL-V8 obtained in Example 6.
[0031] Figure 5 This is the TGA spectrum of Form I of GL-V8 obtained in Example 1.
[0032] Figure 6 This is the TGA spectrum of Form II of GL-V8 obtained in Example 6. DETAILED DESCRIPTION
[0033] The technical scheme of the present invention is further illustrated by specific examples below, but the protection scope of the present invention is not limited thereto. The experimental methods in the following examples are conventional methods unless otherwise specified. The test materials used in the following examples are purchased from conventional biochemical reagent stores unless otherwise specified.
[0034] The analysis and detection conditions of the present invention are as follows:
[0035] The X-ray powder diffraction pattern of the present invention is collected on a Malvern Panalytical X-ray powder diffractometer. The parameters of the X-ray powder diffraction method of the present invention are as follows:
[0036] X-ray reflection parameters: Cu, K-α radiation
[0037] Kα1 1.54060:Kα2 1.54443
[0038] Kα2 / Kα1 intensity ratio: 0.50000
[0039] Voltage: 45 kilovolts (kV)
[0040] Current: 40 milliamperes (mA)
[0041] Scanning range: from 3.0 to 50.0 degrees
[0042] Step size: 0.026°
[0043] The differential scanning calorimetry (DSC) diagram of the present invention is collected on TA DSC-Q2000. The method parameters of the differential scanning calorimetry (DSC) of the present invention are as follows:
[0044] Heating rate: 10℃ / min
[0045] Scanning range: 25~260℃
[0046] Protective gas: Nitrogen
[0047] The thermogravimetric analysis (TGA) graph of the present invention was collected on TA TGA Q500, and the method parameters of the thermogravimetric analysis (TGA) of the present invention are as follows:
[0048] Heating rate: 10℃ / min
[0049] Scanning range: room temperature ~ 350℃
[0050] Protective gas: Nitrogen
[0051] Example 1
[0052] The preparation method of GL-V8 crystal form I comprises the following steps:
[0053] Add 5 g of GL-V8 into 5 mL of anhydrous DMF, heat to 70°C until completely dissolved and clarified, slowly add 20 ml of methanol dropwise while stirring, and after the addition, slowly cool to 20°C and stir for 5 hours, filter, wash the filter cake with water, and dry to obtain GL-V8 Form I.
[0054] The GL-V8 Form I solid prepared in this example was subjected to X-ray powder diffraction (XRPD) analysis (eg Figure 1 As shown), DSC analysis (as Figure 3 ) and TGA analysis (as shown Figure 5 shown).
[0055] The X-ray powder diffraction pattern of the Form I solid of GL-V8 described in the present invention is collected on a Malvern Panalytical X-ray powder diffractometer and the data are shown in Table 1 (only the main diffraction peaks are counted).
[0056] Table 1 Powder X-ray diffraction peak values of GL-V8 crystal form I solid sample
[0057]
[0058]
[0059] Form I, when heated to 133.23°C, begins to show an endothermic peak, and its differential scanning calorimetry (DSC) diagram is as follows: Figure 3 As shown; Form I, when heated to 105.04 ° C, loses 2.473% of its weight, and its thermogravimetric analysis (TGA) is as follows Figure 5 As shown; Form I is an anhydrate and a non-solvate.
[0060] Example 2
[0061] The preparation method of GL-V8 crystal form I comprises the following steps:
[0062] Add 2 g of GL-V8 to 10 mL of anhydrous ethanol, heat to 80°C until completely dissolved and clarified, keep warm for half an hour, slowly cool to 20°C and stir for 5 hours, filter, wash the filter cake with ethanol, and dry to obtain GL-V8 Form I.
[0063] Example 3
[0064] The preparation method of GL-V8 crystal form I comprises the following steps:
[0065] Add 2 g of GL-V8 into 10 ml of anhydrous methanol, heat to 65°C until completely dissolved and clarified, keep warm for half an hour, slowly cool to 20°C and stir for 5 hours, filter, wash the filter cake with methanol, and dry to obtain GL-V8 Form I.
[0066] Example 4
[0067] The preparation method of GL-V8 crystal form I comprises the following steps:
[0068] Add 1 g of GL-V8 to 20 ml of isopropanol, heat to 100°C until completely dissolved and clarified, then keep warm for half an hour, slowly cool to 60°C and stir for 1 hour, filter, wash the filter cake with methanol, and dry to obtain GL-V8 Form I.
[0069] Example 5
[0070] The preparation method of GL-V8 crystal form I comprises the following steps:
[0071] Add 1 g of GL-V8 into 10 ml of THF, heat to 35°C until completely dissolved and clarified, keep warm for half an hour, slowly cool to -20°C, stir for 0.5 hour, filter, wash the filter cake with methanol, and dry to obtain GL-V8 Form I.
[0072] Example 6
[0073] The preparation method of GL-V8 crystal form II comprises the following steps:
[0074] Add 5 g of GL-V8 to 25 mL of ethanol, heat to 80°C until completely dissolved and clarified, slowly add 25 mL of water dropwise while stirring, and after the addition, slowly cool to 20°C and stir for 5 hours, filter, wash the filter cake with water, and dry to obtain GL-V8 Form II.
[0075] The GL-V8 crystal form II solid prepared in this example was subjected to X-ray powder diffraction (XRPD) analysis (eg Figure 2 As shown), DSC analysis (as Figure 4 ) and TGA analysis (as shown Figure 6 shown).
[0076] The X-ray powder diffraction pattern of the Form II solid of GL-V8 described in the present invention is collected on a Malvern Panalytical X-ray powder diffractometer and the data are shown in Table 2 (only the main diffraction peaks are counted).
[0077] Table 2 Powder X-ray diffraction peak values of GL-V8 crystal form II solid sample
[0078]
[0079] Crystal form II, when heated to 124.38°C, begins to show an endothermic peak, and its differential scanning calorimetry (DSC) diagram is as follows: Figure 4 As shown; Form II, when heated to 105.04 ° C, loses 2.518% of its weight, and its thermogravimetric analysis (TGA) is as follows Figure 6 As shown; Form II is an anhydrate and non-solvate.
[0080] Example 7
[0081] The preparation method of GL-V8 crystal form II comprises the following steps:
[0082] Add 2 g of GL-V8 into 10 mL of DMF, heat to 70 °C until completely dissolved, slowly add 10 mL of water while stirring, slowly cool to 20 °C, stir for 5 hours, filter, wash the filter cake with a small amount of water, and dry to obtain GL-V8 crystal form II.
[0083] Example 8
[0084] The preparation method of GL-V8 crystal form II comprises the following steps:
[0085] Add 2 g of GL-V8 into 10 mL of THF, heat to 65°C, and heat and stir until completely dissolved and clarified. Slowly add 10 mL of water while stirring, slowly cool to 20°C, and stir for 5 hours. Filter with suction, wash the filter cake with a small amount of water, and dry to obtain GL-V8 crystal form II.
[0086] Example 9
[0087] The preparation method of GL-V8 crystal form II comprises the following steps:
[0088] Add 1 g of GL-V8 to 20 mL of acetone, heat to 35 °C, heat and stir until completely dissolved and clarified, slowly add 1 mL of water while stirring, slowly cool to -20 °C and stir for 2 hours, filter, wash the filter cake with a small amount of water, and dry to obtain GL-V8 crystal form II.
[0089] Example 10
[0090] The preparation method of GL-V8 crystal form II comprises the following steps:
[0091] Add 1 g of GL-V8 to 10 mL of acetone, heat to 100 °C, and heat and stir until completely dissolved and clarified. Slowly add 3 mL of water while stirring, slowly cool to 60 °C, and stir for 1 hour. Filter with suction, wash the filter cake with a small amount of water, and dry to obtain GL-V8 crystal form II.
[0092] Experimental Example 1 Hygroscopicity experiment of GL-V9 crystal form I and crystal form II:
[0093] Take a dry stoppered glass weighing bottle (outer diameter 50mm, height 15mm), and place it in an artificial climate box (set temperature 25℃±1℃, relative humidity 80%±2%) one day before the test. Accurately weigh the weight (19072.83mg), take the GL-V8 crystal form I prepared in Example 1 and spread it in the above weighing bottle, with a thickness of about 1mm, and accurately weigh the weight (19953.49mg). Open the weighing bottle and place it with the bottle cap under the above constant temperature and humidity conditions for 24 hours. Cover the weighing bottle lid and accurately weigh the weight (19970.36mg).
[0094] Weight gain percentage = (19970.36mg-19953.49mg) / (19953.49mg-19072.83mg)×100%=1.8%
[0095] Take a dry stoppered glass weighing bottle (outer diameter 50mm, height 15mm), and place it in an artificial climate box (set temperature 25℃±1℃, relative humidity 80%±2%) one day before the test. Accurately weigh the weight (18790.55mg), take the GL-V8 crystal form II obtained in Example 6 and spread it in the above weighing bottle, with a thickness of about 1mm, and accurately weigh the weight (19775.73mg). Open the weighing bottle and place it with the bottle cap under the above constant temperature and humidity conditions for 24 hours. Cover the weighing bottle lid and accurately weigh the weight (19795.70mg).
[0096] Weight gain percentage = (19775.70mg-19775.73mg) / (19775.73mg-18790.55mg)×100%=2.0%
[0097] Definition of hygroscopic weight gain (Guidelines for hygroscopicity test of drugs in Appendix 9103 of the 2020 edition of the Chinese Pharmacopoeia, experimental conditions: 25℃±1℃, 80% relative humidity):
[0098] Deliquescent: Absorbs sufficient water to form a liquid.
[0099] Highly hygroscopic: weight gain due to moisture absorption is not less than 15%.
[0100] Hygroscopic: Weight gain due to moisture absorption is less than 15% but not less than 2%.
[0101] Slightly hygroscopic: weight gain due to moisture absorption is less than 2% but not less than 0.2%.
[0102] No or almost no hygroscopicity: weight gain due to moisture is less than 0.2%.
[0103] The results show that the crystal form I of Example 1 of the present invention gains 1.8% in weight after equilibrium at 80% relative humidity, which is slightly hygroscopic; the crystal form II of Example 6 gains 2.02% in weight after equilibrium at 80% relative humidity, which is hygroscopic.
[0104] Experimental Example 2 Stability experiment of GL-V8 crystal form I / II:
[0105] About 300 mg of the GL-V8 crystal form samples prepared in Example 1 and Experimental Example 6 were taken and placed in an open state at 25°C, 60% RH and 40°C, 75% RH, and the XRPD and HPLC purity of the crystal form I samples were measured after 30 days. The experimental results are shown in Table 3.
[0106] Table 3 GL-V8 crystal stability
[0107]
[0108] GL-V8 HPLC test conditions:
[0109] The chromatographic conditions were as follows: octadecylsilane bonded silica gel as filler (Waters XBridge C18, 4.6×250 mm, 5 μm or a chromatographic column of equivalent performance); pH 3.0 phosphate buffer (0.01 mol / L potassium hexafluorophosphate solution) as mobile phase A, acetonitrile as mobile phase B, and elution according to Table 4 below; detection wavelength was 274 nm, column temperature was 40°C; injection volume was 10 μl; flow rate was 1.o ml / min.
[0110] Table 4 Elution program
[0111] Time (minutes) A(%) B(%) 0 62 38 20 62 38 30 40 60 35 25 75 40 25 75 40.1 62 38 48 62 38
[0112] The results show that the crystal forms of GL-V8 I and II are stable and almost unchanged in purity after being placed under 25°C, 60% RH and 40°C, 75% RH conditions for 30 days (see Figure 1 , Figure 2 ).
[0113] The above shows and describes the basic principles, main features and advantages of the present invention. However, the above is only a specific embodiment of the present invention, and the technical features of the present invention are not limited thereto. Any other implementation methods derived by any technician in the field without departing from the technical solution of the present invention should be included in the patent scope of the present invention.
Claims
1. A GL-V8 crystal form, which is crystal form I, has an X-ray powder diffraction spectrum detected by Cu-Ka radiation. θ There are diffraction peaks at 4.0914°, 6.8803°, 9.4388°, 12.5661°, 13.8249°, 16.0123°, 19.1575°, 22.5009°, 23.5099°, 24.0082°, 24.5017°, and 25.6877°. θ The value accuracy is ±0.2°.
2. The GL-V8 crystal form according to claim 1, characterized in that: According to differential scanning calorimetry analysis, an endothermic peak begins to appear when Form I is heated to 133.23°C.
3. The GL-V8 crystal form according to claim 1, characterized in that: According to thermogravimetric analysis, when Form I is heated to 105.04°C, the weight loss is 2.473%.
4. The GL-V8 crystal form according to claim 1, characterized in that: Form I is an anhydrate and a non-solvate.
5. The method for preparing the GL-V8 crystal form according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: Add GL-V8 to solvent a; heat to 35-100°C, slowly drop solvent b, keep warm and stir; slowly cool to -20-60°C, stir for 0.5-5 hours, precipitate solid, filter and dry to obtain GL-V8 crystal form I, wherein solvent a is selected from one or a mixture of two or more of ethanol, methanol, isopropanol, DMF, DCM, THF or acetone, and solvent b is selected from one or a mixture of two or more of methanol, isopropyl ether or methyl tert-butyl ether; Alternatively, add GL-V8 to solvent a, heat to 35-100°C and then keep warm; slowly cool to -20-60°C, stir for 0.5-5 hours, precipitate solid, filter and dry to obtain GL-V8 crystal form I; Among them, the volume ratio of solvent a to solvent b is 1:1-10; the mass volume ratio of GL-V8 to solvent a is 1:1-20, and the unit is g / mL.
6. A GL-V8 crystal form, which is crystal form II, has an X-ray powder diffraction spectrum detected by Cu-Ka radiation, 2 θ There are diffraction peaks at 4.2870°, 6.5855°, 9.5828°, 11.4800°, 13.1891°, 17.9260°, 18.3199°, 21.9220°, 22.6016°, 24.5669°, 24.8689°, 26.6093°, and 27.5103°. θ The value accuracy is ±0.2°.
7. The GL-V8 crystal form according to claim 6, characterized in that: According to differential scanning calorimetry analysis, an endothermic peak began to appear when Form II was heated to 124.38°C.
8. The GL-V8 crystal form according to claim 6, characterized in that: According to thermogravimetric analysis, when Form II is heated to 105.04°C, the weight loss is 2.518%.
9. The GL-V8 crystal form according to claim 6, characterized in that: Form II is an anhydrate and a non-solvate.
10. The method for preparing the GL-V8 crystal form according to any one of claims 6 to 9, characterized in that: The method comprises the following steps: Add GL-V8 to solvent c; heat to 35-100°C, slowly add water, keep warm and stir; slowly cool to -20-60°C, stir for 0.5-5 hours, precipitate solid, filter and dry to obtain GL-V8 crystal form II, wherein solvent c is selected from ethanol, methanol, isopropanol, acetone, DMF or THF, a mixture of one or more thereof; The volume ratio of solvent c to water is 1:1-5; the mass volume ratio of GL-V8 to solvent c is 1:1-20, and the unit is g / mL.
Citation Information
Patent Citations
Flavone compound with antineoplastic activity, preparation thereof and uses thereof
CN101486703A